Analisa Konsentrasi Logam Cd Pada Rhizophora.Sp Menggunakan Metode AAS Di Kawasan Pelabuhan Gilimanuk Jembrana Bali - Karel Yesaya Mbaba; Ida Bagus Made Suryatika; I Gusti Agung Putra Adnyana (Universitas Hamzanwadi, 2019)
In this study, research was conducted on the analysis of Cu concentrations in mangrove plants (Rhizophora.sp) using the Atomic Absorbtion Spectrophotometry (AAS) method in the Gilimanuk Jembrana port area of Bali. The research was conducted on June 23, 2019 until July 28, 2019 in the Faculty of Mathematics and Natural Sciences, Udayana University. The method used is Atomic Absorption Spectrophotometry (AAS), a principle that is based on the process of absorption of energy by atoms that are at the level of basic energy (groundstate). The sample used is in the form of root stems and leaves of mangroves that are cleaned and destroyed in advance, because AAS can only analyze the material in the form of liquid. The results of the analysis with AAS are the Cd metal content at Gilimanuk port has exceeded the threshold of the quality standard that is in accordance with sea water quality standards according to Environmental Decree Number: KEP-MEN LH No.51 / Men KLH / 2004 Cd threshold for tourism marine is 0,002 ppm and for biota is 0,001 ppm, while mangrove is included in marine tourism with a threshold of 0,002 ppm.